Potentials of Low-Budget Microdrones: Processing 3D Point Clouds and Images for Representing Post-Industrial Landmarks in Immersive Virtual Environments - Weißmann, Marco; Edler, Dennis; Rienow, Andreas (Frontiers in Robotics and AI, 2022)
Post-industrial areas in Europe, such as the Rhine-Ruhr Metropolitan region in Germany, include cultural heritage sites fostering local and regional identities with the industrial past. Today, these landmarks are popular places of interest for visitors. In addition to portable camera devices, low-budget ultra-lightweight unmanned aerial vehicles, such as micro quadcopter drones, are on their way to being established as mass photography equipment. This low-cost hardware is not only useful for recreational usage but also supports individualized remote sensing with optical images and facilitates the acquisition of 3D point clouds of the targeted object(s). Both data sets are valuable and accurate geospatial data resources for further processing of textured 3D models. To experience these 3D models in a timely way, these 3D visualizations can directly be imported into game engines. They can be extended with modern interaction techniques and additional (semantic) information. The visualization of the data can be explored in immersive virtual environments, which allows, for instance, urban planners to use low-cost microdrones to 3D map the human impact on the environment and preserve this status in a 3D model that can be analyzed and explored in following steps. A case example of the old wage hall of the Zeche “Bonifacius” (Essen, Germany) with its simple building structure showed that it is possible to generate a detailed and accurate 3D model based on the microdrone data. The point cloud which the 3D model of the old wage hall was based on represented partly better data accuracy than the point clouds derived from airborne laser scanning and offered by public agencies as open data. On average, the distance between the point clouds was 0.7 m, while the average distance between the airborne laser scanning point cloud and the 3D model was −0.02 m. Matching high-quality textures of the building facades brings in a new aspect of 3D data quality which can be adopted when creating immersive virtual environments using the Unity engine. The example of the wage hall makes it clear that the use of low-cost drones and the subsequent data processing can result in valuable sources of point clouds and textured 3D models.